THE CPA EXAMINATION. - Quin, Dick D. (The Accounting Review, 1943)
Abstract The article presents a discussion on testing the ability of the prospective candidate to enter the public accounting field, by examining the certified public accountant (CPA) examination standards in the U.S. The standard examination given by forty-six state and territorial accounting boards is prepared by the Board of Examiners of the American Institute of Accountants. Both educators and public practitioners have a definite part to play in preparing the candidate for the CPA examination. This brings up a very controversial subject, since most educators feel that the college graduate should be permitted to sit for the examination without experience, whereas most public practitioners lean to the belief that a man must have public accounting experience before he should become eligible for the examination. Presenting his opinion the author says that no candidate should be permitted to sit for the CPA examination until he has had a minimum of two years' public experience, or five years' private accounting experience.